Front Cover: Heat‐Triggered Crystallization of Liquid Crystalline Macrocycles Allowing for Conductance Switching through Hysteretic Thermal Phase Transitions (Chem. Asian J. 1/2019). Issue 1 (17th December 2018) - Muraoka, Takahiro; Shima, Tatsuya; Kajitani, Takashi; Hoshino, Norihisa; Morvan, Estelle; Grélard, Axelle; Dufourc, Erick J.; Fukushima, Takanori; Akutagawa, Tomoyuki; Nabeya, Kota; Kinbara, Kazushi
Abstract : A macrocyclic amphiphile, consisting of aromatic groups and oligoethylene glycol chains, exists in a highly ordered columnar–lamellar liquid crystal (LC) phase at room temperature and shows phase‐transition to nematic LC phases followed by crystallization before melting. While the macrocycle returns to the LC phase after cooling from the isotropic liquid, it retains the crystallinity after cooling from the thermally induced crystal. Thanks to this bistability, conductance switching was successfully demonstrated, leading to a universal molecular design for switchable and memory materials, by means of hysteretic phase‐transition processes. More information can be found in the Full Paper by Takahiro Muraoka, Kazushi Kinbara et al. onpage 141 in Issue 1, 2019 (DOI:10.1002/asia.201801372 ).